(3JMaI GdCNjGQ aj GdQO Ydi GdbGFdjf HYOe GdYed HGdXf hbWYjI GdCNHGQs - (3GdCQGfj, GdcGTGfj, eMeO Ydj Hf eMeO MSf, cGf MjG (B1243 (3g`s ((3QeVGf Ydj Hf Ydj QVG GdcdHGjcGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3Efg bO WGd GdJTGLQ Hjf YdeGFfG GdeYGUQjf aj MLjI GdXf hYOegG aefge ef PgH Edi Cf GdCUd MQeI GdYded HGdXf EdG eG NQL HGdOdjd hefge ef YcS abGd HCf GdCUd MLjJfg hhLhH GdYed Hg (B...s
(3BNQgG (B:s
... (3hGYde jG CNj Cfj bO JJHYJ ZGjI GdJJHY hGSJbQjJ fgGjI GdGSJbQGA hLeYJ dCaj gPg GdQSGdI LejY eG bjd aj eSFdI MLjI GdXf hGWdYJ Ydjg Edi GdBf hHGdZJ aj GJeGe GdCOdI (B...(3hddg GdMeOs
(3efbhdI Yf eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\537s
(3GdPQjYI (B3\1501s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs